Effect of cellulose derivative matrix and oligosaccharide on the solid state and physical characteristics of dimethyldioctadecyl ammonium-liposomes for vaccine - Helmy Yusuf, NIDN. 0015077901 (Wolters Kluwer Health - Medknow, 2019)
The present study was to investigate the effect of cellulose matrix and oligosaccharide on solid state and morphology characteristics of freeze-dried cationic dimethyldioctadecylammonium (DDA)-based liposomes encapsulating ovalbumin (OVA). The OVA-containing liposomes were protected using cellulose derivative matrix and oligosaccharide. Despite the fact that saccharides are known to preserve protein and lipid membranes during drying, however, collapse structure are often addressed. In other side, cellulose matrix potentially prevents collapsing as it has been widely used for matrix in drug delivery formulations to increase the mass for compact matrices of resultant products. Their solid state characteristics were determined in terms of their crystallinity using X-Ray diffraction (XRD), thermal properties and detection of phase separation using differential scanning calorimetry (DSC). Furthermore, their morphology was observed using scanning electron microscopy and transmission electron microscopy. The study revealed that formulation with either oligosaccharide and cellulose matrix demonstrated a miscible mixture with DDA and soy phosphatidylcholine (SPC) that might construct stable dried liposomal formulation. Phase separation was not observed in formula with combination of oligosaccharide and cellulose matrix where their DSC thermograms showed glass transition indicating amorphous structure and miscible mixture. XRD confirmed the absence of crystal-like properties, demonstrating prevented crystallization. The dry products were porous with spherical liposomes trapped in the matrices, signifying the ease in reconstitution. Furthermore, OVA were well-preserved as its recovery was more than 80%. The preservation of both liposomes and protein antigen were found to be dependent upon the incorporation of both oligosaccharide and cellulose matrix included in the formulation.